Board of directors, audit committee characteristics and performance of Saudi Arabia listed companies - Al-Matari, Yahya Ali; Al-Swidi, Abdullah Kaid; Fadzil, Faudziah Hanim; Al-Matari, Ebrahim Mohammed (2012)
This study examines the relationship between the internal corporate governance mechanism related to the board of directors, the audit committee characteristics and the performance of the Saudi companies listed in the Saudi stock exchange (TADAWL) in 2010, excluding financial companies. The statistical results of the study are not in line with the agency theory that board of directors and audit committee might mitigate agency problems leading to reduced agency cost by aligning the interests of controlling owners with those of the company.While audit Committee size (ACSIZE) is found to have a significant relationship with firm performance (but in the opposite direction to expectation), other hypothesized variables, the proportion of non-executive directors (BODCOM), CEO Duality (DUAL), Board Size (BSIZE), Audit Committee Independence (ACIND), audit committee meeting (ACMEET) were found to be as expected directions but insignificantly related to firm performance measure except the direction of the proportion of non-executive directors (BODCOM) was opposite to the expectations.